Analyzing the Application of Void Decks on High-rise Affordable Housing in Jakarta, Indonesia, to Achieve Optimal Urban Ventilation - Megan Afkasiga Ririhena; Nedyomukti Imam Syafii (Universitas Gadjah Mada, 2021)
Economic growth in ASEAN countries encourages significant urbanized growth. In line with the growth of urbanization, large swathes of residential buildings have been constructed in urban areas, especially, in the case of Indonesia, through the government's 1000 rusun (high-rise affordable housing) development program in Jakarta. In order to reduce energy consumption and create a sustainable rusun, a passive strategy is needed in the form of natural air conditioning through optimized natural ventilation in these buildings. In this study, testing was conducted on Rusun Rorotan in Jakarta, from two wind source directions (north and northwest) with five void decks configuration samples each, in order to determine wind flow and wind speed patterns in the Rusun area. For this purpose, the wind tunnel simulation method using the Butterfly plugin in Grasshopper was employed. These results should provide a reference for future residential property developers, especially in the scope of other countries in ASEAN, which have similar climatic conditions to that of Indonesia.